Aurelius Augustine and Pelagianism - Cherneva, Dimitria (Forum Theologicum Sardicense, 2025)
Constructed in opposition to the Pelagian heresy, Augustine’s doctrine of man’s free will and God’s grace caused – both in the thinker’s lifetime and in the centuries that followed – not a little controversy and accusations of pre-destination – not only in ecclesiastical but also in philosophical circles. Some theologians have accused Augustine of taking a diametrically opposed position in the context of the dogmatic dispute with Pelagianism – a doctrine that stresses the real self-value of human existence and man’s ability to achieve good on his own (independently) and in his own strength. Accused of going to the extreme of disregarding the freedom of the human will at the expense of grace and divine predestination in order to secure salvation for some and retribution for others – he is considered the forerunner of Calvin’s doctrine of predestination, which many believe paved the way. Does his thought really warrant such assessments, and why do many stumble over it, failing to consider the context in which his doctrine of freedom and grace emerged and unfolded, on the one hand, and its inherently dynamic structure, on the other?